Biosimilar medicines – their use in the treatment of inflammatory bowel diseases. Position statement of the Working Group of the Polish National Consultant in Gastroenterology - Mularczyk, Aldona; Gonciarz, Maciej; Bartnik, Witold; Durlik, Marek; Eder, Piotr; Gąsiorowska, Anita; Linke, Krzysztof; Łodyga, Michał; Łykowska-Szuber, Liliana; Małecka-Panas, Ewa; Pawlik, Magdalena; Radwan, Piotr; et al. (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Biological medical products are drugs whose active components are produced only by living, genetically modified organisms or live cell cultures. Patents and exclusivity for most biopharmaceuticals has either expired or will expire soon, which enables biotechnological companies to introduce similar biological products. The problem of replacing a biological medicine with a biosimilar in the course of therapy remains open. In this statement, the Working Group of the Polish National Consultant in Gastroenterology, in the absence of data regarding bioequivalence in patients with inflammatory bowel disease, does not recommend switching from original biological medicine to its biosimilar analogue in the course of treatment in inflammatory disease patients; however, this may change after receiving the results of controlled studies regarding bioequivalence in this group.